Дослідження рістстимулюючої активності похідних 1,2,4-триазолу на прикладі насіння соняшника простого - Аксьонова, Ілона Ігорівна; Щербина, Роман Олександрович; Панасенко, Олександр Іванович; Книш, Євгеній Григорович; Аксьонов, І. В.; Aksyonova, I. I.; Shcherbyna, R. О.; Panasenko, O. I.; Knysh, Ye. H.; Aksyonov, I. V. (My University, 2014)
Стаття містить результати дослідження рістстимулюючої активності і якісних показників схожості насіння соняшника сорту Прометей, гібридів Купець і Рябота після їх передпосівної обробки сполуками – похідними 1,2,4-триазолу. Серед досліджених речовин виявлені перспективні сполуки в плані подальшого синтезу та отримання нових біологічно активних субстанцій з більш вираженою рістстимулюючою активністю. This article contains the results of investigation of growth-stimulating activity and qualitative indicators of germination of seeds of sunflower of varieties Prometheus, hybrids Kupets and Ryabota after pre-processing of their compounds - derivatives of 1,2.4-triazol. Among the compounds which were investigated detected the promising compounds for the further synthesis and preparation the new biologically active compounds with more growth stimulating activity.
The investigation of growth-stimulating activity of derivatives of 1,2,4-triazole on seeds of sunflower simple
Keywords: 1,2,4-триазол; насіння соняшника; рістстимулююча активність; якісні показники схожості; 1,2,4-triazole; organic synthesis; sunflower; growth-stimulating activity; qualitative indicators of germination